Correlation of Leptin, Insulin and Glucose During Late Gestation and Early Lactation in Murrah Buffaloes - Nagre, S.M.; Kuralkar , Prajakta (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
A study was carried out to assess the levels of Glucose ,Insulin and Leptin during late gestation and early lactation and their correlation in murrah buffaloes was determined. All of the variables were significantly affected by transition period. The level of Insulin, Glucose and Leptin was significantly higher 15 days before parturition, followed by 15 days after parturition and lowest on the day of parturition.
Keywords: Glucose; Insulin; Leptin; Murrah Buffalo; Correlation